Characterization of Selected phenotypes of Khodeiri and Doebli Olive Varieties Using Fractal Geometry in the Syrian Coast (Damascus University Journal of agriculture sciences, 2024)
Many phenotypes of Khodeiri and Doebli olive in Lattakia and tartus. The purpose of this research was to classify selected phenotypes by analyzing characteristics of olive stone computer- image using fractal geometry and moments. Twelve stones from every phenotype, had been imaged,and fractured to extract texture information, moments were used to extract shape.Length, width, shape and texture had been measured, also. The ruselts showed between phenotypes and values (odd ratio 1%) length of stones and regions high biodiversity in Khodeiri and Doebli olive.The Doebli olive phenotypes were divided to two oroups by cluster analysis with degree of similarty 0.47 and The khodeiri olive phenotypes were divided to two groups by cluster analysis with degree of difference 0.97.Fractals and moments found to be a potential technique for accurate, eventual and efficient classification of olive phenotypes and diversity.
Keywords: Fractal geometry; olive; phenotybe; seed lenght; seed width; seed shape